PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN KUB MAMPU JAYA SURABAYA - Yerinda Ritsi Ramadhani; Sulastri Irbayuni (Universitas Islam Kadiri, 2021)
Performance is a evaluate of the eclat of a corporation or organization in achieving the goals that have been set which are usually carried out by human resources. Successful performance requires reliable competence from human resources, besides that compensation is also needed to motivate people to be more enthusiastic about working. In the current era of globalization, especially with the Covid-19 pandemic, MSMEs are required to start from producing quality products to optimizing HR management. These research purpose to decide the impact of competence and remuneration to performance of KUB Mampu Jaya Surabaya employees. These research uses a quantitative method and data collection use a questionnaire in a five-point Likert Scale as a measuring tool. The populace and sample of these study were all employes KUB Mampu Jaya Surabaya, totaling 38 respondents with saturated sampling technique. In this study using primary data. In this study using data analysis techniques is (PLS) Partial Least Square. The results of this study are : 1) The higher the competence of the employees of KUB Mampu Jaya Surabaya, the performance will increase. 2) The higher the competence given by KUB Mampu Jaya Surabaya, the performance will increase. Keywords: Competence, Compensation, Employee Performance